Design and Analysis of Pyramidal Horn Antenna as Plane Wave Source for Anechoic Chamber: Development and Evaluation of a Pyramidal Horn Antenna for Antenna Test Range (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This paper describes the design and analysis of a pyramidal horn antenna having linear polarized, high gain, low side lobes and light in weight. This horn will be used in rectangular antenna test range as source to generate a quasi-plane wave in far field test zone. It specifies the straightforward procedure to determines the physical dimension of pyramidal horn as per the performance specifications generated for antenna test range. The antenna gives 15 dBi gain over 20 bandwidth with center frequency of 10 GHz. HFSS software was used to simulate the design of antenna. Here we describe the estimated dimensions and simulated radiation data.